Proof Carrying Code - Mahajan, Manish (INFOCOMP Journal of Computer Science, 2007)
Proof-Carrying Code (PCC) is a technique that can be used for safe execution of untrusted code. In a typical instance of PCC, a code receiver establishes a set of safety rules that guarantee safe behavior of programs, and the code producer creates a formal safety proof that proves, for the untrusted code, adherence to the safety rules. Then, the receiver is able to use a simple and fast proof validator to check, with certainty that the proof is valid and hence the untrusted code is safe to execute.